EMBRACING WATER-SMART AGRICULTURE FOR OPTIMAL AGRICULTURAL PRODUCTION IN SELECTED AREAS OF BUSHBUCKRIDGE, SOUTH AFRICA (Proceedings of the International Conference on Agriculture, 2022)
Agriculture plays an important role for income generation, economic growth, and employment for majority of people. Agricultural production has become the very means of alleviating poverty. In pursuit to meet the growing demand for food to sustain the ever-growing population, the need to salvage farming and farm productions from extreme climate events using water smart practices remains paramount. The conservation of water resources for a water-scare country, such as South Africa, is important for agricultural development. Water-smart agriculture aims at addressing issues associated with water availability, water use efficiencies as well as water conservation for optimal production. The study was conducted in Chochocho, Bushbuckridge Local Municipality, South Africa. The aim of the study was to examine the adoption of water smart agriculture, and to determine the water use efficient practices employed by farmers in the study area. Random sampling method was employed, and data was collected using structured and semi-structured questionnaires as well as focus group discussion. Furthermore, the descriptive and inferential statistics were used to explain responses from respondents and the Statistical Package for Social Sciences (SPSS version 27) software was used for the analysis. The study found that farmers’ adoption of water smart agriculture practices was hinged on several heterogeneous variables. The study recommends amongst others, the need to conserve water for agricultural production, and water infrastructural development for local food security must be improved. Additionally, water demand and supply management issues must be addressed.
Keywords: Adoption; Water Smart Agriculture; Farmers; Behaviour; Climate change; Productivity